Acne treatment challenges - Recommendations of Latin American expert consensus - Marco Rocha; Franz Barnes; Jemena Calderón; Leonel Fierro-Arias; Carlos Eduardo Montealegre Gomez; Carla Munoz; Obregón Jannell; Patricia Troieli (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background Acne is a chronic inflammatory disorder of the pilosebaceous unit that is associated with a negative impact on quality of life, causing anxiety, depression, and poor self-esteem. The treatment of acne is not simple and presents some new challenges. This article addresses important issues faced by dermatologists on their daily, some of them specific for Latin America. Objective To discuss daily practice recommendations when managing acne patients. Methods A literature review was conducted by a group of eight experts with extensive experience in the field of acne. The results of the data review were presented at an initial kick-off meeting to align the consensus topics. Two e-surveys using the Delphi methodology and an interim group webinar meeting were held. Results The expert panel reached a consensus on all proposed key statements, providing scientific support to help dermatologists and healthcare providers make acne management decisions on topics that can be challenging in the everyday practice of dermatology, such as the characteristics of Generation Z or the importance of the maintenance phase of adult acne treatment. Conclusion This article provides current recommendations for managing acne patients. The high level of agreement achieved based on the latest evidence supports the best acne therapeutic choices in both established topics and new important issues that have emerged in recent years, such as the impact of social media, Generation Z characteristics, and transgender male patient specifics.